Method for producing sodium borohydride
The method of mixing sodium borates, aluminum powders, and fluoride powders in a hydrogen-filled container at controlled temperatures and stirring conditions addresses the inefficiencies of existing sodium borohydride production methods, achieving high reaction rates and efficient production.
Patent Information
- Application Number
- JP2022579472
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-02-05
- Filing Date
- 2022-01-25
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-01-25
AI Technical Summary
Existing methods for producing sodium borohydride are complex, inefficient, and often result in low reaction rates due to issues such as excessive grinding leading to small aluminum particle sizes, destruction of product by grinding media, and the need for high temperatures and pressures.
A method involving the mixing of sodium borates, aluminum powders, and fluoride powders in a closed container filled with hydrogen gas, where the reaction is carried out at 560°C or below, with a stirring mechanism that maintains a specific gap and height ratio to optimize the reaction.
This method allows for the simple and efficient production of sodium borohydride with a high reaction rate, without the need for large facilities, and results in a product with improved properties.
Smart Images

Figure 0007647775000006 
Figure 0007647775000007 
Figure 0007647775000008
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing sodium borohydride, and more particularly to a method for producing sodium borohydride from sodium metaborate. [Background technology]
[0002] Hydrogen fuel is gaining attention as an alternative energy source to fossil fuels, and sodium borohydride (SBH) is a promising hydrogen carrier for hydrogen storage, transportation, and hydrogen generation. In order to popularize sodium borohydride as a hydrogen carrier in society, it is necessary to establish an optimal manufacturing method that takes into account mass production technology.
[0003] As a conventional method for producing sodium borohydride, for example, Patent Document 1 discloses a method for producing sodium borohydride by reacting a trialkyl borate with sodium aluminum hydride.
[0004] Furthermore, Patent Document 2 discloses a method for producing sodium borohydride, which includes a step of reacting sodium metaborate and granular aluminum under a hydrogen atmosphere while rolling and pulverizing them using a stirring medium to obtain sodium borohydride.
[0005] Furthermore, Patent Document 3 discloses a method for producing sodium borohydride, in which the sodium borohydride is rolled and pulverized in a sealed container using ceramic balls as a pulverizing medium.
[0006] Furthermore, Non-Patent Document 1 discloses a method for producing sodium borohydride by reacting sodium diborate (Na4B2O5) and sodium oxide (Na2O) with aluminum and hydrogen in a high-temperature molten state (855 K (581°C), preferably 873 K (599°C)) to obtain sodium borohydride. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent No. 2809666 [Patent Document 2] International Publication No. 2015 / 190403 [Patent Document 3] JP 2019-189483 A [Non-patent literature]
[0008] [Non-Patent Document 1] Bin Hong LIU, and 4 others, “Sodium Borohydride Synthesis by Reaction of Na20 contained Sodium Borate with Al and Hydrogen”, Energy & Fuels, 2007, Vol.21, No.3, p.1707-1711 Summary of the Invention [Problem to be solved by the invention]
[0009] However, the proposal in Patent Document 1 requires converting boric acid into trialkyl borates in advance, and reacting sodium, aluminum, and hydrogen to produce sodium aluminum hydride, which results in a complicated production process.
[0010] In the proposal of Patent Document 2, dried anhydrous sodium metaborate (NaBO2) and aluminum particles with a diameter of approximately 3 mm are charged into a reaction section rotatably arranged in a cylindrical reaction vessel, and sodium borohydride is produced by rolling-pulverization using a stirring medium (steel balls with a diameter of approximately 30 mm) in the reaction vessel. However, there is a problem in that as the rolling-pulverization time increases, the aluminum particles being crushed become too small, making crushing difficult and preventing the reaction from proceeding.
[0011] In the proposal of Patent Document 3, ceramic balls are used as grinding media in a sealed container when producing sodium borohydride. The reaction product becomes denser as a result of rolling-milling, and the ceramic balls continue to break down the product, causing the aluminum particles to become too small in size and shape to be able to be ground by rolling-milling. When this occurs, new surfaces necessary for the reaction cannot be generated, the reaction stops, and the reaction rate drops.
[0012] In the proposal of Non-Patent Document 1, sodium hydroxide is added to sodium metaborate and heated to form an aqueous solution, which is then heated and dehydrated to produce synthesized sodium oxide (Na2O) or sodium diborate (Na4B2O5) containing sodium metaborate, which is then reacted in a molten state under a high pressure of 2.3 MPa. In order to melt sodium diborate, a high temperature (around 855 K (581°C), preferably 873 K (599°C)) is required, and in order to obtain a high reaction rate of 65.8%, the molar ratio of sodium metaborate to sodium oxide needs to be 3:2. If the molar ratio is reduced, the reaction rate drops sharply, and there is a drawback in that the reaction rate of sodium metaborate alone in a solid state at the temperature is zero.
[0013] The present invention has been made in consideration of the above-mentioned problems in the conventional art, and has an object to provide a method for producing sodium borohydride that can achieve the production of sodium borohydride with a simple configuration. [Means for solving the problem]
[0014] The first aspect of the method for producing sodium borohydride is characterized in that, when sodium borates, aluminum powder, and fluoride powder are mixed in a sealed container filled with hydrogen gas and reacted at 560°C or less, stirring is performed in the sealed container using a stirrer, and a stirring height ratio (X), expressed by the following mathematical formula (I) based on the minimum gap (a) between the stirrer and the bottom of the sealed container in the gravity direction and the raw material introduction height (b) at which the raw materials are introduced into the sealed container, is 75% or more. X = [(ba) / b] × 100 ... Formula (I)
[0015] In the first embodiment, the sodium borates may be one or more selected from sodium metaborate and sodium tetraborate.
[0016] In the first embodiment, the fluoride may be one or more selected from sodium fluoride (NaF), sodium hexafluoroaluminate (Na3AlF6), potassium fluoride (KF), potassium aluminum fluoride (KAlF4), aluminum fluoride (AlF3), and lithium fluoride (LiF).
[0017] In the first embodiment, the aluminum in the aluminum powder may have a molar ratio of aluminum to boron in the sodium borates of 4 / 3 or more.
[0018] In the first embodiment, an alkali metal oxide or an alkaline earth metal oxide may be further added, so that the molar ratio of the sum of the molar amounts of the alkali metal and alkaline earth metal and the alkali metal and alkaline earth metal contained in the sodium borates to the molar amount of boron contained in the sodium borates is 1.0 or more and 1.4 or less.
[0019] In the first embodiment, the inside of the sealed container may be heat-treated at 280° C. or more and 560° C. or less before stirring. Effect of the Invention
[0020] According to the first aspect, it is possible to provide a method for producing sodium borohydride without using large-scale facilities. [Brief description of the drawings]
[0021] [Figure 1] FIG. 1 is a process diagram for producing sodium borohydride (SBH) using sodium borates as raw materials. [Figure 2A]FIG. 2A is a reaction schematic diagram illustrating the steps of a sodium borohydride (SBH) production reaction. [Figure 2B] FIG. 2B is a reaction schematic diagram illustrating the steps of a sodium borohydride (SBH) production reaction. [Figure 2C] FIG. 2C is a reaction schematic diagram illustrating the steps of a sodium borohydride (SBH) production reaction. [Figure 2D] FIG. 2D is a reaction schematic diagram illustrating the steps of a sodium borohydride (SBH) production reaction. [Figure 2E] FIG. 2E is a reaction schematic diagram illustrating the steps of a sodium borohydride (SBH) production reaction. [Figure 2F] FIG. 2F is a reaction schematic diagram illustrating the steps of a sodium borohydride (SBH) production reaction. [Diagram 3] FIG. 3 is a partial cross-sectional view showing an example of a sealed container used in this embodiment. [Figure 4] FIG. 4 is a partial cross-sectional view showing an example of a sealed container used in this embodiment. [Diagram 5] FIG. 5 is a partial cross-sectional view showing another example of the sealed container used in this embodiment. [Figure 6] FIG. 6 is a partial cross-sectional view showing another example of the sealed container used in this embodiment. [Figure 7] FIG. 7 is a partial cross-sectional view showing another example of the sealed container used in this embodiment. [Figure 8] FIG. 8 is a partial cross-sectional view showing another example of the sealed container used in this embodiment. [Figure 9] FIG. 9 is a SEM backscattered electron image of the product when the reaction temperature was 510° C. [Figure 10] FIG. 10 is a SEM backscattered electron image of the product when the reaction temperature was 478° C. [Figure 11] FIG. 11 is an X-ray diffraction analysis chart of a product obtained when the reaction was stopped at a reaction rate of 8.1% immediately after the start of the reaction under the same conditions as in Test Example 18. [Figure 12A]FIG. 12A is an SEM mapping photograph of a product in which the reaction was stopped at a reaction rate of 8.1% immediately after the start of the reaction, when the reaction was conducted under the same conditions as in Test Example 18. [Figure 12B] FIG. 12B is an SEM mapping photograph of a product in which the reaction was stopped at a reaction rate of 8.1% immediately after the start of the reaction, when the reaction was conducted under the same conditions as in Test Example 18. [Figure 13] FIG. 13 is an X-ray diffraction analysis chart of the product in Test Example 20 with a reaction rate of 91.1%. [Figure 14] FIG. 14 is an X-ray diffraction analysis chart of the product of Comparative Example 10 in which NaOH was added and the reaction rate was 14.1%. [Figure 15] FIG. 15 is an SEM mapping photograph of the product in Comparative Example 10 to which NaOH was added and at a reaction rate of 14.1%. [Figure 16] FIG. 16 is a diagram showing the relationship between the height ratio ((ba) / b) and the elapsed reaction time. [Figure 17] FIG. 17 is a diagram showing the relationship between the reaction rate (SBH rate) and the elapsed reaction time. [Figure 18] FIG. 18 is a diagram showing the production conditions of Test Example 22. [Figure 19] FIG. 19 is a diagram showing the production conditions of Test Example 23. [Figure 20A] FIG. 20A is a photograph showing the appearance of a stirring rod equipped with a pin-shaped stirring bar, using the sealed container (gap a: 4 mm) shown in FIG. [Figure 20B] FIG. 20B is a photograph of the product after rotating the stir bar to produce sodium borohydride. [Figure 20C] FIG. 20C is a photograph of the product peeled off from the container after stirring for a predetermined period of time. [Figure 20D] FIG. 20D is a photograph measuring the thickness of the resulting product. [Figure 20E] FIG. 20E is a magnified photograph of the resulting product. [Figure 20F] FIG. 20F is a SEM photograph of a cross section of a product lump with a reaction rate of 91.1%. [Figure 21A]FIG. 21A is a photograph of the product after sodium borohydride was produced by rotating a stirring rod using the sealed container (gap a: 5 mm) shown in FIG. [Figure 21B] FIG. 21B is an enlarged photograph of the state of the product after stirring for a predetermined period of time. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] <First embodiment> FIG. 1 is a process diagram for producing sodium borohydride (SBH) using sodium borates as raw materials. In the method for producing sodium borohydride according to the first embodiment, sodium borates, aluminum powder, and fluoride powder are mixed in a sealed container filled with hydrogen gas and reacted at 490°C to 560°C. The sodium borates and aluminum powder react in a solid phase. As shown in FIG. 1, the method for producing sodium borohydride according to the first embodiment includes a first step (S-11) to a third step (S-13).
[0023] Specific examples of sodium borates 51 as the boric acid raw material in the first step include borax (sodium tetraborate: Na2B4O7), sodium metaborate (NaBO2 (=Na2B2O4)), and combinations thereof, but are not limited to these.
[0024] In this embodiment, the Na / B (molar ratio) of the sodium borates is preferably in the range of more than 0.85 and not more than 1.5, more preferably more than 1.0 and not more than 1.4, as shown in the test examples described later.
[0025] Each step will be described in detail below. In the following steps, sodium metaborate (NaBO2) separated as crystals will be used as the sodium borate.
[0026] [1st step] The first step (S-11) is a step of introducing a non-oxidizing gas 53 into a sealed container after or before charging sodium metaborate having a particle size of 100 μm or less, aluminum powder 52, and fluoride 54, which are sodium borates 51, into the sealed container, to fill the inside with a non-oxidizing gas atmosphere. The first process is mainly for preparing and charging the raw materials. In this first step, the sealed container is filled with a non-oxidizing gas, thereby preventing moisture in the air from adhering to the surface oxide film of the sodium borate and aluminum. The timing for filling the sealed container with a non-oxidizing gas may be before or after the raw materials are charged into the sealed container.
[0027] Here, examples of the non-oxidizing gas 53 include hydrogen gas and rare gases (e.g., helium gas, argon gas, etc.) Alternatively, the first step may be a step of creating a vacuum state in the sealed container after or before sodium borate having a particle size of 100 μm or less and aluminum are charged into the sealed container.
[0028] The sealed container used must have heat and pressure resistance sufficient to withstand high temperatures (eg, 560° C.) and high pressures (eg, 10 MPa), and must be able to secure an airtight space for filling with gas. A container equipped with at least a stirring means may also be used. Details of such a closed container will be described later.
[0029] The sodium borates used as raw materials are preferably at least one selected from sodium metaborate, sodium tetraborate, and sodium diborate.
[0030] Hereinafter, an explanation will be given using sodium metaborate powder as an example of sodium borates. In this embodiment, the particle size of the sodium metaborate powder is 100 μm or less. If the particle size of the sodium metaborate powder exceeds 100 μm, the production efficiency of sodium borohydride may decrease. The sodium metaborate powder is an undersize raw material obtained by pulverizing the powder to a certain degree and then passing it through a sieve with an opening of 100 μm. In order to further improve the production efficiency of sodium borohydride, it is preferable to use sodium metaborate powder with a smaller particle size. To this end, the sodium metaborate powder may be used that has been sieved through a sieve with an opening of less than 100 μm (for example, a sieve with an opening of 50 μm or less).
[0031] The mass of sodium metaborate charged in the first step can be determined according to the desired amount of sodium borohydride to be produced. However, since sodium metaborate contains moisture, it is necessary to estimate the amount of sodium metaborate more than necessary in consideration of the weight loss due to the moisture.
[0032] The aluminum raw material may be fragments such as powder material, scrap material, etc. Although the aluminum fragments may be scrap material such as cutting chips and waste materials, it is preferable to select aluminum fragments with as low a content of impurities of metals nobler than aluminum as possible.
[0033] The average particle size of the aluminum to be charged is, for example, 1 μm or more, and the maximum particle size is preferably 10 mm or less. If the average particle size of the aluminum is less than 1 μm, dust explosions are likely to occur, making it difficult to handle, and the particles may easily adhere to each other and clump together. If the average particle size is greater than 10 mm, the specific surface area per mass becomes small, the reaction area decreases, and the initial reaction rate may drop drastically. The average particle size is more preferably 5 μm or more and 5 mm or less. The average particle size is obtained as the particle size of the sphere-equivalent diameter using a laser diffraction particle size distribution measuring device.
[0034] The fluoride raw material is at least one selected from sodium fluoride (NaF), sodium hexafluoroaluminate (Na3AlF6), potassium fluoride (KF), potassium aluminum fluoride (KAlF4), aluminum fluoride (AlF3), and lithium fluoride (LiF). Among these, sodium fluoride, which is an alkali metal fluoride, is particularly preferred.
[0035] The reason for adding fluoride here is to improve the reaction rate of sodium borohydride and increase the particle stirring reaction efficiency. The fluoride in the reaction process forms an alkali metal and an alkali aluminum fluoride layer during the reduction reaction of alkali metal oxide that occurs on the surface of aluminum. Since the free energy of formation of sodium fluoride is low and stable, the fluoride layer serves to maintain a fluoride atmosphere inside the aluminum particles.
[0036] The "particle agitation reaction" caused by the addition of fluoride will be explained. In the early stage of the reaction, aluminum (Al) and sodium metaborate (NaBO2) come into contact with each other through stirring, and sodium metaborate adheres to the aluminum (Al) particles. This adhesion causes the oxide film on the aluminum (Al) surface to absorb sodium oxide (Na2O), which is converted into needle-shaped iota-alumina (Iota-alumina: 0.67Na 6Al 9.33O) by the catalytic action of fluoride ions. Iota-alumina is known as a precursor of beta-alumina in low-temperature beta-alumina synthesis methods such as the sol-gel method. Iota-alumina has a structure and ion permeability similar to beta-alumina. This allows sodium ions in particular to easily pass through the oxide film on the aluminum (Al) surface. This iota-alumina forms a layer on the surface of the aluminum (Al).
[0037] Inside the thin (5 to 10 nm) oxide layer that turns into iota-alumina and is formed in the early stages of the reaction, sodium oxide (Na2O) becomes sodium (Na) through the reduction action of aluminum (Al), and sodium (Na) becomes sodium hydride (NaH) when reacted with hydrogen (H2).
[0038] On the other hand, because of the high concentration of Na ions, the aluminum oxide (Al2O3) produced at the same time is immediately neutralized to sodium oxide (Na2O) and becomes sodium aluminum dioxide (NaAlO2). When fluoride ions are present, sodium aluminum dioxide (NaAlO2) crystallizes into iota alumina (0.67Na 6Al 9.33O) due to its catalytic action, and sodium oxide (Na2O) is discharged. This iota alumina is a needle-shaped crystal.
[0039] It is speculated that the reason why iota alumina becomes needle-like crystals is due to a reaction in which sodium oxide (Na2O) is expelled during the crystallization process as the crystals grow. In other words, it is speculated that the crystals grow preferentially in directions with low sodium oxide (Na2O) concentrations, so iota alumina extends in one direction and becomes needle-like crystals.
[0040] Sodium hydride (NaH) passes through the layer of iota alumina and migrates to the surface of the aluminum particles, where it comes into contact with sodium metaborate (NaBO2) and reacts to produce sodium borohydride (SBH) and sodium oxide (Na2O).
[0041] At temperatures above 490°C, which is the necessary condition for the reaction, sodium borohydride (SBH) becomes molten, so it acts as a solvent for sodium hydride (NaH) and sodium oxide (NaO) and serves as a mass transfer medium that fills the iota alumina layer.
[0042] In addition, when sodium borohydride (SBH) becomes molten, it becomes easier for it to bond with sodium metaborate (NaBO2). The sodium hydride (NaH) contained in sodium borohydride (SBH) reacts with sodium metaborate (NaBO2), producing sodium borohydride (NaBH4) and sodium oxide (Na2O). The sodium oxide (Na2O) returns to the aluminum particles through particle contact caused by stirring, and becomes the raw material for sodium hydride.
[0043] On the other hand, in the layer of iota-alumina that has grown into a needle shape, it is presumed that sodium ions can move at the highest speed, but when sodium borohydride (SBH) is mainly contained in the gaps between the needle crystals, the gaps between the needle crystals become passageways for sodium ions, boron ions, oxygen ions, aluminum ions, and fluoride ions. Therefore, when sodium ions, boron ions, oxygen ions, aluminum ions, and fluoride ions pass through the iota-alumina layer, a conversion reaction to sodium borohydride (SBH) occurs even inside the iota-alumina layer.
[0044] As described above, by satisfying the conditions for reaction inside and outside the iota-alumina layer of aluminum (Al) particles and on the surface of sodium metaborate (NaBO2) particles, aluminum (Al) particles containing products and intermediate products and sodium metaborate (NaBO2) particles come into contact with each other through stirring. As a result, high-speed movement and uniform mixing of sodium borohydride (SBH), sodium hydride (NaH), sodium oxide (NaO2), sodium metaborate (NaBO2), and aluminum ions to each particle is realized, which is not possible with a simple diffusion reaction, and the sodium borohydride (SBH) production reaction is promoted.
[0045] The action of fluoride is not only to promote the crystallization of iota alumina as mentioned above, but also to form a layer of NaAlF (a mixture of cryolite, sodium fluoride, and aluminum fluoride) on the surface of aluminum, which reacts with aluminum to produce low-grade aluminum fluoride (AlF 1.5 (Presumably, the aluminum fluoride reduces sodium oxide together with hydrogen to produce sodium hydride, aluminum oxide, and sodium fluoride. The aluminum fluoride can move via sodium borohydride. Furthermore, when the concentration or temperature of the aluminum fluoride and sodium hydride increases, some of them evaporate, making it possible for them to move in the gas phase. These actions allow sodium hydride to move or be produced in places other than the aluminum surface, accelerating the reaction to produce sodium borohydride and contributing to an improvement in the reaction rate. 2AlF 1.5 +3Na2O+3 / 2H2→3NaF+3NaH+Al2O3...(1)
[0046] Under these conditions, the sodium hydride (NaH) production reaction occurs mainly on the surface of the aluminum (Al) particles, while the sodium borohydride (SBH) and alumina production reactions can occur inside the iota-alumina layer, outside the iota-alumina layer, and on the sodium metaborate (NaBO2) particles.
[0047] The raw material sodium metaborate (NaBO2) and the intermediate product sodium oxide (Na2O) are also circulated by coming into contact with aluminum (Al) particles.
[0048] In this embodiment, this state in which contact between particles causes repeated mass transfer not only inside the aluminum (Al) particles but also between the raw material sodium metaborate (NaBO2) and sodium borohydride, which is the transfer medium for the intermediate product, and rapid reactions occur on the surface and within each particle is hereinafter referred to as a "particle stirring reaction."
[0049] Next, a detailed description will be given with reference to reaction diagrams (FIGS. 2A to 2F) showing the process of producing sodium borohydride (SBH) using sodium fluoride (NaF) as a fluoride. FIG. 2A to FIG. 2F are reaction diagrams showing the process of the reaction of producing sodium borohydride (SBH). Here, the reason for adding fluoride (e.g., sodium fluoride: NaF) is to improve the reaction rate of sodium borohydride, as described above. Fluoride has two effects on aluminum. The first effect is to promote the crystallization of alumina, and the second effect is to form a NaAlF layer on the surface of aluminum, supply a strong reducing substance to the outside of the aluminum particles, and promote reduction.
[0050] 1) Initial mixing stage -1 As shown in FIG. 2A, particles of the three components (aluminum (Al) 101, sodium metaborate (NaBO2) 102, and sodium fluoride (NaF) 103) come into contact with each other, causing separation and adhesion between the particles.
[0051] 2) Initial mixing stage -2 As shown in FIG. 2B, a dense Al oxide film (Al2O3·H2O) 101b is formed on a surface 101a of an aluminum (Al) 101 grain by natural oxidation. This dense Al oxide film 101b formed by natural oxidation has a thickness of about 0.01 μm. The dense Al oxide film 101b on the surface of the aluminum particle releases water at high temperatures (up to 300°C) and, with the aid of the crystallization-promoting effect of sodium fluoride (NaF) 103, is further transformed into iota alumina, changing into a needle-like iota alumina (0.67Na 6Al 9.33O) layer 101c.
[0052] 3) Initial reaction stage-3 As shown in FIG. 2C, inside the needle-shaped iodine alumina layer 101c, hydrogen ions (H + ), sodium ion in sodium metaborate (Na +) ions are mobile. The transferred hydrogen ions and sodium ions initiate a reaction inside the needle-shaped iota-alumina layer 101c, and the reaction products, sodium borohydride (SBH) 111 and sodium hydride (NaH) 112, seep out of the needle-shaped iota-alumina layer 101c. Then, the diffusion of sodium oxide (Na2O) 113 inside and outside the iota-alumina (0.67Na 6Al 9.33O) layer 101c progresses.
[0053] 4) Mid-phase reaction As shown in FIG. 2D, hydrogen ions (H + ), sodium ion (Na + ), aluminum ion (Al 3+ ), metaborate ion (BO2 - ), oxygen ions (O 2- ) move, and reactions begin inside and outside the needle-like iota-alumina layer 101c, producing reactant layers (sodium borohydride (SBH) 111, sodium hydride (NaH) 112) 115.
[0054] 5) Peak reaction period As shown in Figure 2E, the particle stirring reaction causes the particles of the three components to repeatedly come into contact with each other, supplying sodium metaborate (NaBO2) 102 to the aluminum 101 particles, and the reaction products (sodium borohydride (SBH) 111, sodium hydride (NaH) 112) are transferred from the aluminum 101 particles to the sodium metaborate (NaBO2) 102 at high speed due to the particle stirring.
[0055] 6) End of reaction As shown in FIG. 2F, the entire aluminum 101 particle becomes the reaction product sodium borohydride (SBH) 111 and a needle-like iota alumina layer 101c.
[0056] In the first step (S-11), the temperature inside the sealed container when the raw materials are charged is not particularly limited, and may be less than 100°C. The temperature inside the sealed container can be room temperature since there is no need to heat it. In addition, in order to avoid a reaction between sodium metaborate and moisture in the air, it is necessary to seal the container promptly after charging the raw materials.
[0057] In addition, in the production of sodium borohydride, aluminum is consumed by oxidation, so aluminum is charged into the sealed vessel in the first step so that the molar ratio of aluminum to boron in sodium metaborate is 4 / 3 or more. The amount of aluminum powder is preferably 120% or more by molar ratio relative to the amount required for the synthesis of sodium borohydride. Although a part of the excess aluminum is consumed by reaction with moisture, it also contributes to increasing the opportunity for contact with sodium metaborate when the amount of aluminum as a raw material decreases as the reaction proceeds, thereby improving the reaction rate.
[0058] [Second process] As shown in FIG. 1, the second step (S-12) is a step in which, after the first step, the contents in the sealed container are heat-treated at 280° C. or higher and 560° C. or lower without stirring, to react the residual moisture contained in the sodium metaborate and aluminum powder with the aluminum and convert them into hydrogen gas and aluminum oxide. That is, this step is a step of removing moisture from within the reaction system by reacting the evaporated moisture, i.e., the moisture remaining in the sealed container, with aluminum, or by degassing with a vacuum pump.
[0059] In this process, when aluminum reacts with water, aluminum oxide and hydrogen gas are generated. More specifically, vaporized water vapor passes through the aluminum oxide film, and aluminum reacts with water to produce aluminum oxide and hydrogen gas. The reaction between water and aluminum is shown in the following reaction formula (2). 2Al+3H2O → Al2O3+3H2 (2) Normally, the oxide layer on aluminum has defects that allow gas to pass through. Water vapor reaches the aluminum substrate and oxidizes it, producing hydrogen gas.
[0060] Regarding the heating conditions in the second vaporization step, if the heating conditions are 280°C or higher, sodium metaborate hydrate will completely release water, but since crushed sodium borate powder is prone to adsorb moisture and the desorption temperature is high, it is desirable to carry out dehydration drying at 400°C or higher, which allows the moisture in the atmosphere to be removed in a shorter time.
[0061] In addition, in the second step, pre-baking may be performed by heating in a non-oxidizing atmosphere at 400° C. to 560° C. for 1 hour or more without starting stirring. By performing this pre-baking, the reaction rate in the latter half of the reaction in the next third step can be improved.
[0062] Furthermore, after the first step, without starting stirring, dehydration to remove moisture may be performed in air at 280° C. to 560° C. before this pre-baking, and this moisture removal process may be used in combination with pre-baking.
[0063] [3rd step] As shown in FIG. 1, in this embodiment, after the second step (S-12) is completed, the next third step (S-13) is provided, whereby sodium borohydride can be produced.
[0064] In this embodiment, the reaction of sodium borohydride is carried out by contacting the powders together while still in a solid phase and reacting them on the surface of the aluminum, and then the product and raw materials are transferred by diffusion, allowing the reaction to continue and synthesize the material. In order to further assist this material transfer, kinetic energy can also be applied by stirring.
[0065] As sodium borohydride is produced, the amount of hydrogen in the reaction vessel decreases, but the reaction rate can be increased by increasing the hydrogen gas pressure. The reaction is shown in the following reaction equation (3). 4Al+6H2+3NaBO2→3NaBH4+2Al2O3...(3)
[0066] In the third step, the sealed container used in the first and second steps may be used as it is, or a different sealed container may be used. That is, the first to third steps may be carried out in one sealed container, or may be carried out in a different sealed container.
[0067] The hydrogen gas pressure maintained in the third step is preferably in the range of 0.4 MPa to 10 MPa, more preferably in the range of 0.5 MPa to 10 MPa, and even more preferably in the range of 0.7 MPa to 10 MPa. By maintaining the hydrogen gas pressure at 0.3 MPa to 10 MPa, the production efficiency of sodium borohydride is excellent, and a reaction vessel, equipment, etc. having excellent pressure resistance is not required, and an increase in equipment costs can be suppressed.
[0068] In the third step, in order to allow the reaction to proceed sufficiently, the heating temperature is preferably 490° C. or higher and 560° C. or lower. By setting the heating temperature to 490° C. or higher and 560° C. or lower, a sufficient reaction rate can be obtained, the efficiency of producing sodium borohydride is excellent, and sublimation of the produced sodium hydride and sodium borohydride is suppressed, resulting in a sufficient recovery rate.
[0069] Here, the reaction temperature is set to 490°C or higher in order to form needle-like iota alumina and to make the product, sodium borohydride (SBH), melt to promote the reaction. That is, even if the reaction is performed at less than 490°C, the oxide film of aluminum (Al) is converted to iota alumina, but the rate of iota alumina formation is very slow, and the thin and long so-called needle-like iota alumina formed at 490°C or higher changes to short iota alumina. Also, at temperatures less than 490°C, sodium borohydride (SBH) does not melt, so it becomes solid and passes through the iota alumina layer more slowly, and the amount of sodium borohydride that seeps out of the aluminum (Al) particles together with sodium hydride (NaH) is greatly reduced. Therefore, most of the reaction occurs inside the aluminum (Al) particles as a reaction between boron ions that have passed through the iota alumina layer and sodium hydride (NaH), and the product reaction is not sufficiently promoted.
[0070] Here, the state of the needle-shaped alumina layer and sodium borohydride (SBH) at different reaction temperatures is compared in Figs. 9 and 10. The black material on the outside of the particles in Figs. 9 and 10 is the dispersed carbon. Fig. 9 is an SEM backscattered electron image of the product when the reaction temperature is 510°C. Fig. 10 is an SEM backscattered electron image of the product when the reaction temperature is 478°C. As shown in Fig. 9, a needle-shaped iota-alumina layer is formed around the central aluminum (Al), and sodium borohydride (SBH) fills the inner layer, outer layer, and inner layer of the iota-alumina layer. When the reaction temperature is 510°C, sodium borohydride (SBH) penetrates the iota-alumina layer as a melt and seeps out to the outside, bonding the surrounding sodium metaborate (NaBO2) particles.
[0071] On the other hand, as shown in FIG. 10, when the reaction temperature is set to 478° C., since the reaction temperature is less than 490° C., sodium borohydride (SBH) is present in large amounts inside the iota alumina layer. Furthermore, there are many voids in the outer acicular iota alumina layer. It is presumed that diffusion and movement is not possible in the voids, resulting in an extremely slow reaction rate. In Figure 10, a small amount of sodium borohydride can be seen on the outside. This is presumed to be sodium borohydride produced by the reaction of sodium hydride gas that has diffused as a gas or low-grade aluminum fluoride gas with boric acid.
[0072] Sodium borohydride (SBH) can be produced by the above first to third steps.
[0073] Furthermore, after the third step, a fourth step (hereinafter, after-baking) may be performed as a post-treatment in which the temperature of the third step is maintained. This fourth step may be continued in the agitated sealed container of the third step, or may be transferred to a non-agitated sealed container and continued.
[0074] Next, we will explain the time (time lag) from the start of stirring to the start of reaction in the third process. In the third process, the time until the start of reaction is called the time lag. The minimum total amount of sodium hydride (NaH) and sodium borohydride (SBH) required to start the particle stirring reaction relative to the total amount of raw materials to be reacted is a hydrogen reduction of 2.5 to 3.5%, which corresponds to the amount of boron (B) in the raw materials. The proportion of these hydrides can be measured by the hydrogen reduction.
[0075] The time lag described here is the time from the start of stirring until the reaction rate reaches 3%. The reaction rate until the start of particle stirring reaction is very slow. This is due to the presence of an aluminum oxide film formed on the surface of aluminum (Al) particles. In other words, the aluminum oxide film (estimated to be 5 to 10 nm) is a very strong barrier to mass transfer. When sodium oxide (Na2O) diffuses into the inside of the aluminum particle, the aluminum oxide film becomes an oxide film containing sodium oxide (Na2O). When sodium oxide (Na2O) reaches the inside of this oxide film layer and reacts with aluminum (Al), sodium oxide (Na2O) is reduced and sodium (Na) and alumina (Al2O3) are produced. Sodium (Na) reacts with hydrogen (H2) to become sodium hydride (NaH), and sodium hydride (NaH) moves to the outside of the oxide film layer and reacts with sodium metaborate (NaBO2) to produce sodium borohydride (SBH).
[0076] The aluminum oxide (Al2O3) on the inside of the oxide film reacts with sodium oxide (Na2O) to become sodium aluminum dioxide (NaAlO2), but the presence of fluoride ions promotes the needle-like crystallization of iota-alumina (0.67Na 6Al 9.33O), changing into a thick needle-like iota-alumina layer.
[0077] It was found that when the ratio of these changed aluminum (Al) particles reached a reaction rate of approximately 3%, calculated as the amount of hydrogen reduction relative to the raw material, the "particle stirring reaction" proceeded very quickly.
[0078] In the above embodiment, the sodium metaborate and the aluminum powder may be charged separately into the sealed container, or may be charged into the sealed container as a mixture containing them. When charging as a mixture, it is preferable to provide a step of mixing the sodium metaborate and the aluminum powder to obtain a mixture before the first step, and to charge the sodium metaborate and the aluminum powder in the form of the mixture into the reaction container in the first step. By mixing the aluminum powder and the sodium metaborate in advance and using the raw material in a mixed state, the initial reaction rate can be increased. In addition, when aluminum powder and sodium metaborate are mixed, they can be dispersed and mixed in advance and then pressed into a mold to form pellets. Pellets have the advantage that they are less likely to absorb moisture than powders and are easier to handle.
[0079] The fluoride, sodium metaborate and aluminum powder may be charged separately in the sealed container, or the fluoride and aluminum may be mixed together first, the fluoride may be attached to the surface of the aluminum, and then the sodium metaborate may be charged. Alternatively, they may be charged as a mixture containing them.
[0080] By adding sodium fluoride (NaF) as a fluoride to sodium metaborate powder, the molar ratio of the alkali metal to the boron in sodium borate and the sodium contained in the sodium borate (hereinafter referred to as Na / B (molar ratio)) becomes 1 or more, thereby improving the reaction rate of sodium borohydride. Here, the Na / B (molar ratio) is preferably greater than 1 and equal to or less than 4.
[0081] Here, the method of the present embodiment is a reaction system of aluminum powder (solid), sodium metaborate powder (solid), fluoride powder (solid), and hydrogen (gas). In this reaction system, in order for the reaction to proceed well, two things are necessary: removing the oxide film on the surface of the aluminum particles, and supplying transfer energy to make the concentration of the raw material or product in the solid uniform in order to proceed with the reaction.
[0082] In order to remove the effects of the initial aluminum oxide film, the oxide film on the aluminum surface must be scratched by stirring, forming a new surface where the raw material comes into contact with the aluminum and the reaction begins, or sodium oxide must diffuse and penetrate the oxide film, forming iota alumina, allowing the metal ions to diffuse. The period until this reaction begins is the induction period.
[0083] Once the reaction begins, sodium oxide (Na2O) is supplied to the surface of the aluminum, where it is reduced to aluminum, producing sodium hydride. Then, sodium borohydride acts as an adhesive, and the aluminum particles and sodium metaborate particles exchange sodium hydride for sodium metaborate. This causes the sodium hydride and sodium metaborate to react, further producing sodium borohydride. In this way, particle agitation reactions, in which the reaction proceeds very quickly when particles are stirred and mixed, do not require stirring using a medium, and the reaction proceeds simply by particles coming into contact with each other.
[0084] Next, an example of a sealed container that can be used in this embodiment will be described, but this embodiment is not limited to the following.
[0085] FIG. 3 is a partial cross-sectional view showing an example of a sealed container used in this embodiment. 3, the sealed container 10A has a cylindrical container body 12 with a round bottom and a removable disk-shaped lid 14 that seals the container body 12. A temperature-adjustable heater 16 is disposed on the outside of the lower part of the container body 12, and the contents of the container body 12 are heated by the heater 16. An O-ring 18 is disposed on the upper end surface of the container body 12 in close contact with the lid 14 to ensure internal airtightness, and when the lid 14 is closed, the lid 14 is in close contact with the O-ring 18 against the container body 12.
[0086] The lid 14 has an opening in its center, a cylindrical part is erected near the opening, and a motor 20 is disposed on the upper side of the cylindrical part. The stirring device is composed of the motor 20, a stirring rod 22 connected to the rotating shaft of the motor 20, and a plurality of pin-shaped stirring bars 22A provided in a direction perpendicular to the axis of the stirring rod 22. When the lid 14 is attached to the container body 12, the tip of the stirring rod 22 reaches the lower region inside the container body 12. In other words, when the motor 20 is driven, the pin-shaped stirring bars 22A rotate together with the stirring rod 22, and the contents of the container body 12 are stirred.
[0087] The lid 14 is further provided with a first pipe 24 and a second pipe 30 which communicate with the inside of the container body 12, and the first pipe 24 is connected to a hydrogen gas supply source (not shown) via a hydrogen gas supply valve 26 and to a vacuum pump (not shown) via an exhaust valve 28. That is, when the hydrogen gas supply valve 26 is opened, hydrogen gas is supplied into the container body 12, and when the exhaust valve 28 is opened, the inside of the container body 12 is degassed. In addition, the second pipe 30 is connected to a pressure gauge 32, and the pressure inside the container body 12 can be known by the pressure gauge 32.
[0088] Also, as shown in FIG. 3, the minimum gap (a) between the stirrer 22A and the inner circumferential surface of the container body 12 of the sealed container 10A is set to 0 mm to 4 mm as shown in the test example described later. This is to make the stirring height ratio, which determines the size of the container in the test example, the amount of raw material, and the bulk density, 75% or more. When the gap a between the lowest part 22a and the inner circumferential surface 12b of the bottom of the container is set to 4 mm or less, the raw material 39 is stirred by the pin-shaped stirrer 22A of the stirring rod 22, and sodium metaborate (NaBO2) fragments adhere to the minimum amount of aluminum (Al) particles required to start the reaction, and the oxide film of the aluminum (Al) particles becomes iota alumina, and sodium hydride (NaH) and sodium borohydride (SBH) required for the entire aluminum (Al) particles to react are generated. Before this reaction begins, there is a long run-up period, known as the time lag mentioned above. However, once the reaction of sodium hydride (NaH) begins, sodium borohydride (SBH) acts as a mass transfer medium for sodium hydride (NaH) on the aluminum (Al) surface, and a very rapid reaction to produce sodium borohydride (SBH) occurs on all particles.
[0089] When the reaction rate is between 40% and 60%, the proportion of sodium borohydride (SBH) increases and it acts as an adhesive. The particles covered with the product then tend to stick together and form a ball. In the case of a short pin-type stirrer, there is no force pushing against the wall, so the ball that forms becomes like bread dough and holds together.
[0090] In addition, since the pin-shaped stirrer has a small cross-sectional area and is short, only a small amount of product adheres to the stirrer. The product is moved by the pin like bread dough, and the reaction continues in a mass transfer state that is slower than the particle stirring state but faster than diffusion transfer in a stationary state, resulting in a relatively high reaction speed and reaction rate.
[0091] In contrast, when the gap a between the lowermost portion 22a of the stirring rod 22 and the inner peripheral surface 12b of the bottom portion 12a of the container body 12 is set to 5 mm or more, as in the case of the sealed container 10A shown in FIG. 3, the stirring strength decreases, the proportion of the oxide film of the aluminum (Al) particles that becomes iota alumina decreases, the generation of sodium hydride (NaH) and the formation of the iota alumina layer become small, and the time lag of the reaction becomes large, the reaction cannot start within a practical time, and the reaction rate drops drastically.
[0092] In addition, in the sealed container, it is preferable that the stirring height ratio (hereinafter also referred to as "height ratio") is 75% or more. Here, the stirring height ratio refers to the relation ratio when the minimum gap between the stirring bar 22A and the bottom of the sealed container 10A in the gravity direction is a and the raw material introduction height at which the raw material 39 is introduced into the sealed container 10A is b, and is expressed by the following formula (I). X = [(ba) / b] × 100 ... Formula (I) As shown in the test example described later, when the stirring height ratio (X) is 75% or more, the particle stirring reaction is good, but when the stirring height ratio (X) is less than 75%, the particle stirring reaction does not proceed. Note that when the stirring height ratio (X) is 100%, the reaction speed and reaction rate are the highest. For example, when the minimum gap between the stirring bar 22A and the inner peripheral surface of the container body of the sealed container 10A is a = 4 mm, and the height of the raw material poured into the sealed container is b = 17.7 mm, X is 77% (see Test Example 3 described later).
[0093] 20A to 20F are photographs showing an example of the production of sodium borohydride (SBH) using the sealed container 10A (gap a=4 mm) shown in FIG. 3 with a height ratio (X) of 77%. FIG. 20A is a photograph of the stir bar after the stir bar is rotated to produce sodium borohydride (SBH). FIG. 20B is a photograph of the product after the stir bar is rotated to produce sodium borohydride (SBH). FIG. 20C is a photograph of sodium borohydride (SBH) peeled off from the container after stirring for a predetermined time. FIG. 20D is a photograph of the thickness of the product obtained. The thickness of the product at the bottom is 4 mm. FIG. 20E is an enlarged photograph of the product obtained. FIG. 20F is a cross-sectional SEM photograph of a lump of product with a reaction rate of 91.1%. It can be seen that the cross section of the lump-shaped product shows that the particulate reaction product is partially bonded to each other, and there are gaps between the particles of the reaction product.
[0094] 21A and 21B are photographs showing an example of the production of sodium borohydride (SBH) using the sealed container 10A (gap a=5 mm) shown in FIG. 3 with a height ratio (X) of 72%. FIG. 21A is a photograph of the product after the stirring bar is rotated to produce sodium borohydride (SBH). FIG. 21B is an enlarged photograph of the product after stirring for a predetermined period of time has been completed.
[0095] As shown in FIG. 16, when the sealed container 10A (height ratio X=77%) shown in FIG. 3 was used, the production of sodium borohydride (SBH) proceeded well. This exceeds the reaction rate of 3% required for the raw material in the cross section being stirred at the start of the reaction to start reacting. The sodium borohydride production reaction proceeded by starting the particle stirring reaction, and some wrinkles were observed on the bottom side of the product after the test as shown in FIG. 20C, and gaps were observed on the cross section of the product as shown in FIG. 20F. This indicates that the adhesive force of the sodium borohydride melt caused the product to become dough-like, and the pin of the stirrer 22A integrated the entire product, while the transfer of material occurred in the product. The transfer rate of material in the stirring that integrated the entire product into a dough-like shape (hereinafter referred to as "bread dough stirring") was slower than the transfer rate of material in the particle stirring reaction, but was faster than the diffusion transfer rate of material in a stationary state. As a result, the particle stirring reaction occurs first, and the product is mixed locally by the adhesion of sodium borate to the aluminum particles. The entire product is then mixed by stirring the dough, achieving a reaction rate of 90% or more for the desired product, sodium borohydride.
[0096] In contrast, when the sealed container 10A shown in FIG. 3 (height ratio X=72%) is used, the diameter of the gap in the center after stirring is the same as the length of the stirring bar, as shown in FIG. 21A, and the diameter of the gap is smaller than that in FIG. 20B. The cross-sectional area of the stirring is reduced, and the stirring strength is reduced, and the raw material on the cross-section being stirred at the start of the reaction cannot exceed the reaction rate of 3% required to start the particle stirring reaction, so the product does not become like so-called bread dough, and the production of sodium borohydride (SBH) was insufficient. As a result, as shown in the comparative example described later, the reaction rate of the target sodium borohydride was also 2% or less (see Comparative Example 1 described later). From FIG. 21B, it can be seen that the product with gap a: 5 mm was in a state of loose powder close to the raw material.
[0097] FIG. 5 is a partial cross-sectional view showing another example of the sealed container used in this embodiment. As shown in FIG. 5, the sealed container 10B is different from the sealed container 10A in FIG. 3 in that the J-shaped stirring part 22B is provided at the lower end of the stirring rod 22 that rotates inside the container body 12. The J-shaped stirring part 22B is formed so as to be curved along the inner circumferential surface of the bottom part 12a of the container body 12. When the raw material is put into the container body 12 and the stirring rod 22 is rotated, the J-shaped stirring part 22B is curved along the inner circumferential surface of the bottom part 12a, so that the raw material is less likely to adhere to the inner wall of the container during stirring. Here, in the sealed container in FIG. 5, the gap a between the J-shaped stirring part 22B and the inner circumferential surface of the bottom part 12a is set to 0 mm to 4 mm.
[0098] Fig. 6 is a partial cross-sectional view showing another example of the sealed container used in this embodiment. The difference from the sealed container 10A in Fig. 3 is that the sealed container 10C has a plurality of scrapers 35 at the lower end of the stirring rod 22 that rotates inside the container body 12, making it a multi-blade. Here, also in the sealed container 10C of FIG. 6, the gap a between the tip of the scraper 35 on the inner peripheral surface side and the inner peripheral surface of the bottom portion 12a is set to 0 mm to 2 mm.
[0099] Fig. 7 is a partial cross-sectional view showing another example of the sealed container used in this embodiment. The difference from the sealed container 10A in Fig. 3 is that the sealed container 10D has a spiral ribbon-shaped scraper 36 at the lower end of the stirring rod 22 that rotates inside the container body 12. Here, in the sealed container 10D in Fig. 7, the gap a between the tip on the inner peripheral surface side of the ribbon-shaped scraper 36 and the inner peripheral surface of the bottom 12a is also set to 0 mm to 2 mm.
[0100] FIG. 8 is a partial cross-sectional view showing another example of the sealed container used in this embodiment. The difference from the sealed container 10A in FIG. 3 is that the sealed container 10E has a horizontal container body 12, and a wide paddle 37 is provided via a support to the stirring rod 22 rotating inside the container body. Here, in the sealed container 10E in FIG. 8, the gap a between the tip of the wide paddle 37 on the inner peripheral surface side and the bottom part 12b of the inner peripheral surface is also set to 2 mm. When the wide paddle 37 as in the sealed container 10E is used for stirring, the paddle surface scoops up the raw material as the wide paddle 37 rotates. While the raw material is being scooped up by this paddle surface or while the scooped raw material falls, the raw material particles collide with each other, and a good particle stirring reaction proceeds.
[0101] <Second embodiment> The method for producing sodium borohydride according to the second embodiment includes steps 1 to 3 described in the method for producing sodium borohydride according to the first embodiment. For each step, the same description as in the first embodiment will be omitted, and only the different contents will be described. In the method for producing sodium borohydride according to the second embodiment, in the first step, an alkali metal hydroxide or an alkali metal oxide is further charged into the sealed container. Then, in the second step, the mixed sodium borate powder, aluminum powder, and alkali metal hydroxide are reacted and dehydrated at 490°C to 560°C in a sealed container filled with hydrogen gas. Alternatively, after heating and vacuum suction dehydration, in the third step, sodium metaborate powder, aluminum powder, and alkali metal oxide are mixed in a sealed container filled with hydrogen gas and reacted at 490°C to 560°C.
[0102] Examples of the hydroxide of a metal having alkaline properties include sodium hydroxide (NaOH), potassium hydroxide (KOH), and lithium hydroxide (LiOH).
[0103] Examples of metal oxides having alkaline properties include sodium oxide (Na2O), lithium oxide (Li2O), sodium aluminum dioxide (NaAlO2), calcium oxide (CaO), strontium oxide (SrO), etc. Calcium oxide is added to increase the alkalinity.
[0104] When sodium hydroxide (NaOH) is used as the hydroxide of an alkaline metal, sodium hydroxide consumes aluminum and hydrogen is supplied to the sealed container instead, as shown in the following reaction formula (3). Therefore, it is preferable to increase the amount of aluminum added by an amount equivalent to the loss due to aluminum consumption. 6NaOH+2Al→2NaAlO2+2Na2O+3H2...(3)
[0105] [Test Examples and Comparative Examples] Hereinafter, the present embodiment will be described in more detail with reference to test examples showing the effects of the present embodiment, but the present embodiment is not limited to these.
[0106] In the following, in Test Example 1 to Test Example 11, Test Example 13 to Test Example 26, and Comparative Examples 1, 3, 4, 7, and 8-11, sodium metaborate (NaBO2) powder was used as sodium borate, and fluoride was added. In Test Example 12 and Comparative Example 2, sodium metaborate (NaBO2) and borax (sodium tetraborate: Na2B4O7) were used in combination as sodium borate. In Comparative Examples 5 and 6, sodium diborate (Na4B2O5) was used as sodium borates. In addition, sodium fluoride (NaF) was used as the fluoride, but in Test Example 10, sodium hexafluoroaluminate (Na3AlF6) was used as the fluoride, and in Test Example 11, aluminum fluoride (AlF3) was used as the fluoride. In Test Example 18 to Test Example 23, and Comparative Examples 8 to 10, sodium hydroxide was added together with fluoride as an additive.
[0107] [Test Example 1] (a) First step In Test Example 1, sodium metaborate powder was used as the boric acid raw material. 5.82 g of sodium metaborate (NaBO2) that was crushed and sieved through a 100 μm mesh size sieve, 3.82 g of aluminum (Al) powder (average particle size 30 μm), and 0.72 g of sodium fluoride (NaF) were mixed and then charged into a sealed container 10A equipped with a pin-shaped stirrer 22A shown in FIG. 3 at room temperature. Next, the inside of the sealed container was connected to a vacuum pump. Here, the gap a between the inner circumferential surface 12b of the container body 12 was set to 0 mm.
[0108] (b) Second step The moisture in the raw materials was removed by connecting the sealed container to a vacuum pump and heating the inside of the container to 520° C. The time from when the temperature reached 500° C. until the third step was completed was 0.4 hours.
[0109] (c) Third step After filling the sealed container with hydrogen gas at 0.74 MPa, the stirring means in the sealed container was rotated, and the stirring rotation speed was set to a peripheral speed of 4.87 cm / s (30 rpm), and the mixture was stirred for 17.9 hours while maintaining the heating temperature at 520°C. The third step was terminated when the stirring time was 20 hours or when the reaction rate calculated from the pressure reduction rate in the sealed container became less than 0.5% / hour, and the mixture was cooled. The maximum hydrogen gas pressure at this time was 0.76 MPa, the minimum was 0.69 MPa, and the hydrogen gas pressure at the end was 0.70 MPa. In this manner, sodium borohydride (SBH) was obtained.
[0110] After the third step, the reaction rate was calculated by calculating the hydrogen gas volume (molar amount) consumed from the standard volume of hydrogen gas, the average temperature and volume in the container, and the hydrogen gas pressure. As a result, the reaction rate (SBH rate) was 93.0%. The reaction rate by iodometric titration was 89.7%. The Na / B (molar ratio) in Test Example 1 was 1.19. The height ratio in Test Example 1 was 100%.
[0111] In addition, the content of sodium borohydride in the reaction product was determined by iodometric titration as shown below, and was found to be the same (89%). The reason why the sodium borohydride production rate by titration is lower than the production rate calculated from the decrease in hydrogen gas is because sodium hydride coexists as a hydride. Since sodium hydride can be converted to sodium borohydride when it comes into contact with boric acid by diffusion or stirring, the reaction rate calculated from the amount of hydrogen consumed was used without correction. In this embodiment, unless otherwise specified, the "reaction rate" is described as the reaction rate (SBH rate) obtained by calculation from the amount of hydrogen consumed, not the reaction rate obtained by iodometric titration.
[0112] ~Iodometric titration method~ (1) 50 mg of sample (reaction product) was weighed out to the nearest 0.1 mg and placed in a weighing bottle. (2) The sample collected in (1) was transferred to a 200-mL Erlenmeyer flask with a stopper. 40 mL of a 20 g / L NaOH solution was added to the Erlenmeyer flask with a stopper, and the flask was heated in a water bath to completely decompose the unreacted aluminum powder. (3) After cooling the decomposition product of (2) to room temperature, 20.0 ml of 0.05 mol / L iodine solution was added using a whole pipette, the tube was sealed, and the tube was left in the dark for 15 minutes. (4) 3 ml of hydrochloric acid was added to the left-standing material (3) and shaken well, after which it was titrated with 0.1 mol / L sodium thiosulfate. (5) The titration was terminated when the purple color of iodine changed to colorless. (6) A blank test was carried out without adding any sample, and the sodium borohydride content was calculated using the following formula: <Formula for calculating sodium borohydride content> NaBH4 (mass%)={(AB)×0.1×f×37.83 / 8} / C×100 The variables and constants in the above formula are as follows: A: Blank test 0.1 mol / L sodium thiosulfate solution titration value (ml) B: Titration value of the sample solution with 0.1 mol / L sodium thiosulfate solution (ml) f: Factor of 0.1 mol / L sodium thiosulfate solution C: Sample amount (mg) 37.83: Molecular weight of sodium borohydride (g / mol) 8: Normality (N) of 1 mol / L sodium borohydride solution
[0113] [Test Example 2] Sodium borohydride (SBH) was obtained in the same manner as in Test Example 1, except that the gap a between the inner circumferential surface 12b of the container body 12 was set to 2 mm. As a result, the reaction rate (SBH rate) was 92.9%. The Na / B (molar ratio) of Test Example 2 was 1.19. The height ratio of Test Example 2 was 89%.
[0114] [Test Example 3] Sodium borohydride (SBH) was obtained in the same manner as in Test Example 1, except that the gap a between the inner circumferential surface 12b of the container body 12 was set to 4 mm. As a result, the reaction rate (SBH rate) was 93.2%. The height ratio of Test Example 3 was 77%.
[0115] [Test Example 4] Instead of the sealed container 10A shown in FIG. 3 in Test Example 1, a sealed container 10C equipped with a J-shaped stirring section 22B in FIG. 5 was used, the gap (a) was set to 1 mm or less (a part of it contacted the inner circumferential surface of the bottom), the heating temperature in the third step was set to 518°C, and stirring was changed to 20.5 hours. Except for this, sodium borohydride (SBH) was obtained in the same manner as in Test Example 1. As a result, the reaction rate (SBH rate) was 95.1%. The height ratio of Test Example 4 was 100%.
[0116] [Test Example 5] Instead of the sealed container 10A shown in FIG. 3 of Test Example 1, a horizontal sealed container 10E equipped with a wide paddle (WP) 37 shown in FIG. 8 was used, and 17.46 g of sodium metaborate (NaBO2), 17.46 g of aluminum (aluminum (Al) powder having an average particle size of 30 μm, and 2.17 g of sodium fluoride (NaF) were mixed and then charged into the sealed container 10E. Except for changing the heating temperature in the third step to 517° C. and the stirring time to 13 hours, the same operation as in Test Example 1 was performed to obtain sodium borohydride (SBH). As a result, the reaction rate (SBH rate) was 94.1%. The height ratio of Test Example 5 was 87%. Here, the gap a between the inner circumferential surface 12b side of the container body 12 was 2 mm.
[0117] [Test Example 6] In Test Example 5, 1.08 g of sodium fluoride (NaF), half the amount of Test Example 5, was mixed, and then, in the third step, the heating temperature was changed to 510°C and stirring was changed to 23.4 hours, and the same operation as in Test Example 1 was performed to obtain sodium borohydride (SBH). As a result, the reaction rate (SBH rate) was 90.4%. The Na / B (molar ratio) in Test Example 6 was 1.10. The height ratio in Test Example 5 was 87%. Here, the gap a with the inner circumferential surface 12b side of the container body 12 was 2 mm.
[0118] [Test Example 7] In the third step of Test Example 5, the heating temperature was changed to 549°C and the stirring time was changed to 23.3 hours, and the same operation as in Test Example 1 was performed to obtain sodium borohydride (SBH). The Na / B (molar ratio) in Test Example 3 was 1.19. As a result, the reaction rate (SBH rate) was 81.7%. The height ratio in Test Example 7 was 87%. Here, the gap a with the inner circumferential surface 12b side of the container body 12 was 2 mm.
[0119] [Test Example 8] In Test Example 5, the particle size of aluminum (Al) was changed to 5 μm, the heating temperature was set to 510° C., and the stirring time was set to 6.5 hours, and the same operation as in Test Example 5 was performed to obtain sodium borohydride (SBH). As a result, the reaction rate (SBH rate) was 75.6%. The height ratio of Test Example 8 was 87%. Here, the gap a with the inner circumferential surface 12b side of the container body 12 was set to 2 mm.
[0120] [Test Example 9] In Test Example 6, sodium borohydride (SBH) was obtained by the same operation as in Test Example 6, except that in the third step, the stirring rotation speed was 6 rpm (circumferential speed 1.54 cm / s) for 16.9 hours. The Na / B (molar ratio) in Test Example 9 was 1.19. As a result, the reaction rate (SBH rate) was 86.6%. The height ratio in Test Example 9 was 87%. Here, the gap a with the inner circumferential surface 12b side of the container body 12 was 2 mm.
[0121] [Test Example 10] In Test Example 6, the additive was changed from sodium fluoride (NaF) to sodium hexafluoroaluminate (Na3AlF6), and the additive amount was 1.81. The same operation as in Test Example 6 was performed to obtain sodium borohydride (SBH). The Na / B (molar ratio) in Test Example 8 was 1.10. As a result, the reaction rate (SBH rate) was 85.3%. The height ratio in Test Example 10 was 87%. Here, the gap a with the inner peripheral surface 12b side of the container body 12 was 2 mm.
[0122] [Test Example 11] Sodium borohydride (SBH) was obtained by the same operation as in Test Example 6, except that the additive was changed from sodium fluoride (NaF) to aluminum fluoride (AlF3) and the amount added was 1.44 g. The Na / B (molar ratio) in Test Example 11 was 1.00. As a result, the reaction rate (SBH rate) was 73.4%. The height ratio of Test Example 11 was 87%. Here, the gap a with the inner circumferential surface 12b side of the container body 12 was 2 mm.
[0123] [Test Example 12] In Test Example 5, 6.98 g of sodium metaborate (NaBO2) and 8.01 g of borax were used as boric acid raw materials, and the heating temperature was 510°C. The procedure was the same as in Test Example 6, except that sodium borohydride (SBH) was obtained. The Na / B (molar ratio) in Test Example 11 was 0.89. As a result, the reaction rate (SBH rate) was 56.0%. The height ratio in Test Example 12 was 87%. Here, the gap a between the inner circumferential surface 12b side of the container body 12 was 2 m.
[0124] [Test Example 13] Sodium borohydride (SBH) was obtained by the same operation as in Test Example 2, except that sodium fluoride (NaF) was changed to 1.08 g in Test Example 2. As a result, the reaction rate (SBH rate) was 95.5%. The Na / B (molar ratio) in Test Example 13 was 1.29. The height ratio in Test Example 13 was 89%. Here, the gap a with the inner circumferential surface 12b side of the container body 12 was set to 2 mm.
[0125] The results of these Test Examples 1 to 13 are shown in Table 1.
[0126] [Table 1]
[0127] As shown in Table 1, in Test Examples 1 to 13, the particle stirring reaction caused mass transfer between the raw material sodium metaborate (NaBO2), the intermediate product (NaH, Na2O), and the product (SBH) not only inside the aluminum (Al) particles but also between the particles themselves, resulting in a good SBH conversion rate. In addition, when the gap (a) in the sealed container was 4 mm or less, the particle stirring reaction proceeded effectively, and the production efficiency of sodium borohydride (SBH) was good.
[0128] [Comparative Example 1] In the first step of the test example 1, a sealed container 10A with a gap a of 5 mm shown in FIG. 3 was used, 17.46 g of sodium metaborate (NaBO2), 11.45 g of aluminum powder, and 0.72 g of sodium fluoride (NaF) were added, and the heating temperature in the third step was changed to 520°C. Except for this, the same operation as in the test example 1 was performed to obtain sodium borohydride (SBH). The Na / B (molar ratio) in the comparative example 1 was 1.19. As a result, the reaction rate (SBH rate) was 1.6%. The height ratio in the comparative example 1 was 72%.
[0129] [Comparative Example 2] In the first step of the test example 1, a ceramic ball (diameter 5 mm) was put into the closed container 10A shown in FIG. 3, the weight ratio of the stirring medium to the raw material was set to 48, 1.94 g of sodium metaborate (NaBO2), 0.21 g of sodium diborate (Na4B2O5), 1.27 g of aluminum powder, and 0.206 g of sodium fluoride (NaF) were added, the heating temperature in the third step was changed to 558°C, the peripheral speed was set to 78.5 cm / s (300 rpm), and stirring was performed for 13.8 hours. The same operation as in the test example 1 was performed to obtain sodium borohydride (SBH). The Na / B (molar ratio) in the comparative example 2 was 1.17. As a result, the reaction rate at a reaction rate of 10% was good at 90% / Hr, but the reaction rate at a reaction rate of 0.5 decreased to 2.1% / Hr, and the final reaction rate (SBH rate) was 71.9%. The height ratio in Comparative Example 2 was 100%.
[0130] [Comparative Example 3] In the first step of the test example 1, ceramic balls (diameter 5 mm) were put into the closed container 10A shown in FIG. 3, the weight ratio of the stirring medium to the raw material was set to 48, 1.95 g of sodium metaborate (NaBO2) and 1.12 g of aluminum powder were added, the heating temperature in the third step was changed to 520°C, and the peripheral speed was set to 301 cm / s (1150 rpm). Except for this, the same operation as in the test example 1 was performed to obtain sodium borohydride (SBH). The Na / B (molar ratio) in the comparative example 3 was 1.00. As a result, the time lag was the shortest at 0.33 hours, but the reaction rate (SBH rate) was 21.9%. The height ratio in the comparative example 3 was 100%.
[0131] [Comparative Example 4] In Test Example 5, the particle size of aluminum (Al) was changed to 90 μm, and the heating temperature was changed to 510° C., and the same operation as in Test Example 5 was performed to obtain sodium borohydride (SBH). As a result, the reaction rate (SBH rate) was 37.8%. The height ratio of Comparative Example 4 was 87%. Here, the gap a with the inner circumferential surface 12b side of the container body 12 was set to 2 mm.
[0132] [Comparative Example 5] In the first step of the test example 5, a sealed container 10C with a multi-blade (MB) equipped with a plurality of scrapers 35 as shown in FIG. 6 was used, 5.88 g of sodium diborate (Na4B2O5), 2.555 g of aluminum powder, and 1.65 g of sodium fluoride (NaF) were added, and the heating temperature in the third step was changed to 530°C, and the peripheral speed was changed to 78.5 cm / s (300 rpm). Except for this, the same operation as in the test example 1 was performed to obtain sodium borohydride (SBH). The Na / B (molar ratio) in the comparative example 5 was 2.65. As a result, the reaction rate at a reaction rate of 0.1 was 12.3% / Hr, and the reaction rate (SBH rate) was 72.6%. The height ratio of the comparative example 5 was 89%. Here, the gap a between the inner peripheral surface 12b side of the container body 12 was set to 2 mm.
[0133] [Comparative Example 6] In the first step of the test example 5, the sealed container 10C shown in FIG. 6 was used, 5.88 g of sodium diborate (Na4B2O5), 2.54 g of aluminum powder, and 0.22 g of sodium fluoride (NaF) were added, and the heating temperature in the third step was changed to 530°C, and the peripheral speed was changed to 78.5 cm / s (300 rpm). Except for this, the same operation as in the test example 1 was performed to obtain sodium borohydride (SBH). The Na / B (molar ratio) in the comparative example 6 was 2.09. As a result, the reaction rate at a reaction rate of 0.1 was 13.2% / Hr, and the reaction rate (SBH rate) was 73.2%. The height ratio of the comparative example 6 was 89%. Here, the gap a between the inner peripheral surface 12b side of the container body 12 was set to 2 mm.
[0134] The results of Comparative Examples 1 to 6 are shown in Table 2.
[0135] [Table 2]
[0136] In Comparative Example 1, the gap (a) was 5 mm or more and the height ratio was 72%, so the particle stirring reaction did not proceed smoothly as in Test Examples 1 to 4 where the height ratio was 75% or more, and a product could not be obtained.
[0137] In Comparative Example 2, when producing sodium borohydride, ceramic balls were used as grinding media in a closed vessel and soft stirring was performed, so that a reaction similar to a particle stirring reaction occurred in the early stages of the reaction, but the ceramic balls destroyed the product, and the product continued to be compressed in the closed vessel, forming a compressed layer made of the product, and the diffusion reaction became dominant. As a result, the reaction rate and sodium borohydride (SBH) reaction rate decreased. In Comparative Example 3, the peripheral speed was fast and rolling grinding was performed, so the aluminum particles were deformed, and the time lag was short at 0.33 Hr, but the reaction rate immediately decreased. In addition, since no fluoride was added, the final sodium borohydride (SBH) reaction rate also decreased significantly.
[0138] In Comparative Example 4, when producing sodium borohydride, the particle size of aluminum (Al) particles was set to 90 μm, so the reaction surface area was reduced and the reaction rate of sodium borohydride (SBH) was significantly reduced, with the reaction rate at a reaction rate of 0.1 being as low as 17% / Hr, and the reaction rate 22 hours after the start of stirring being as low as 0.7% / Hr. After the end of the reaction, the reaction rate was 37.8%, and the iodine titration reaction rate was 37.5%, both of which were significantly reduced.
[0139] In Comparative Examples 5 and 6, sodium diborate is used as sodium fluoride and sodium borates, and the Na / B ratio is 2 or more, so that the aluminum oxide coating on the surface of the aluminum (Al) particles becomes a sodium aluminum dioxide (NaAlO2) layer. Even if sodium aluminum dioxide (NaAlO2) contains fluoride, it cannot become iota alumina at a high Na / B ratio of 1.5 or more, and remains sodium aluminum dioxide (NaAlO2), and some of it becomes xNa2O·Al2O3 and Na2O, which have a higher ratio of sodium oxide than iota alumina. When the Na / B ratio of the raw material is high, the product contains a lot of free sodium oxide (Na2O), and the produced sodium boron (SBH), sodium oxide (Na2O), and sodium hydride (NaH) form a melt, and becomes sherbet-like immediately after the reaction starts. As a result, the reaction rate at a reaction rate of 10% is slowed down because mass transfer occurs due to diffusion in this sherbet-like high-density solid-liquid. In Comparative Example 5, the reaction rate at a reaction rate of 10% was 12.3% / Hr, and the final reaction rate was 72.6%. In Comparative Example 6, the reaction rate at a reaction rate of 10% was 13.2% / Hr, and the final reaction rate was 73.2%. The final reaction rates of Comparative Examples 5 and 6 were both lower than the final reaction rate of 94.1% of Test Example 5, in which the Na / B ratio was 1.19.
[0140] FIG. 16 is a diagram showing the relationship between the height ratio and the elapsed reaction time. In Fig. 16, symbol I indicates the results when the height ratio is 100% (a = 0 mm), symbol II indicates the results when the height ratio is 89% (a = 2 mm), symbol III indicates the results when the height ratio is 77% (a = 4 mm), and symbol IV indicates the results when the height ratio is 72% (a = 5 mm). As shown in Fig. 16, the particle stirring reaction started when the stirring height ratio was 75% or more, but the reaction did not start when the height ratio was 72% or less than 75%. As a result, when the height ratio was 100% (a = 0 mm), the reaction rate and reaction rate were the highest, and the production efficiency of sodium borohydride (SBH) was good when the height ratio was 75% or more.
[0141] [Test Examples 14 to 17, Comparative Example 7] In the third step of Test Example 2, the hydrogen pressure was set to 0.4 MPa to 0.8 MPa, and sodium borohydride (SBH) was obtained by the same operation as in Test Example 1. As a result, the reaction rate (SBH rate) was good, 68.1% when the hydrogen pressure was 0.5 MPa in Test Example 14, 90.0% when the hydrogen pressure was 0.6 MPa in Test Example 15, 92.9% when the hydrogen pressure was 0.7 MPa in Test Example 16, and 95.5% when the hydrogen pressure was 0.8 MPa in Test Example 17. In addition, when the hydrogen pressure in Comparative Example 7 was 0.4 MPa, the reaction rate (SBH rate) was 20.4%. The results of Test Example 2, Test Examples 14 to 17, and Comparative Example 7 are shown in Table 3 and FIG. 17. Here, the gap a between the inner circumferential surface 12b side of the container body 12 was set to 2 mm.
[0142] [Table 3]
[0143] FIG. 17 is a diagram showing the relationship between the reaction rate (SBH rate) and the reaction time. In FIG. 17, symbol V indicates the results when the hydrogen pressure is 0.4 MPa, symbol VI indicates the results when the hydrogen pressure is 0.5 MPa, symbol VII indicates the results when the hydrogen pressure is 0.6 MPa, symbol VIII indicates the results when the hydrogen pressure is 0.7 MPa, and symbol IX indicates the results when the hydrogen pressure is 0.8. As shown in FIG. 17, when the hydrogen pressure is 0.5 MPa or more, the reaction rate (SBH rate) of sodium borohydride (SBH) was good, at 60% or more. In contrast, when the hydrogen pressure is 0.4 MPa, the reaction rate (SBH rate) of sodium borohydride (SBH) was 10.0%. When this hydrogen pressure decreases, hydrogen gas becomes stable due to chemical equilibrium, and the stability of the hydride decreases. At 0.4 MPa, the amount of sodium hydride and sodium borohydride (SBH) produced is small, and particle adhesion and adhesion are difficult to occur, so stirring cannot be performed in areas that the stirring pin cannot reach, and the reaction remains partial, resulting in a decrease in the reaction rate.
[0144] As a result, it was found that the necessary hydrogen pressure is preferably at least 0.5 MPa. Note that the improvement in reaction rate from the inflection point of reaction rate 40% to 60% in the graph of the test example with hydrogen pressure of 0.5 MPa to 0.7 MPa indicates that the stirring reaction changed from a particulate, pin-shaped stirring bar 22A to a total stirring reaction in which the whole is tangled like bread dough.
[0145] Also, when the hydrogen pressure was 0.8 MPa, the initial reaction rate was so fast that the inflection point could not be identified, or it may have started at a fast stage, or the particle stirring state and reaction rate may have been about the same. Furthermore, to obtain a high reaction rate of 90% of sodium borohydride (SBH) by adding fluoride, at least 0.6 MPa is required. In addition, when the hydrogen pressure is 0.8 MPa, there is an effect of increasing the reaction rate of sodium borohydride (SBH) at around 90% reaction rate (SBH rate). This is presumably due to the effect of the chemical equilibrium shifting to the hydride side, increasing the amount of sodium borohydride produced, and in turn increasing the amount of sodium borohydride produced.
[0146] [Test Example 18] In the first step of the test example 1, a sealed container 10C with a multi-blade (MB) equipped with a plurality of scrapers 35 shown in FIG. 6 was used, and 5.82 g of sodium metaborate (NaBO2), 3.18 g of aluminum powder, 0.62 g of sodium fluoride (NaF), and 0.1 g of sodium hydroxide powder were added. The heating temperature in the third step was changed to 531°C, and the peripheral speed was changed to 15.7 cm / s (60 rpm). Except for this, the same operation as in the test example 5 was performed to obtain sodium borohydride (SBH). The Na / B (molar ratio) of the test example 18 was 1.19. As a result, the time lag was 1.14 Hr. The reaction rate at a reaction rate of 10% was 31.3% / Hr. The reaction rate (SBH rate) was 62.2% when the stirring time was 5 hours. The height ratio of the test example 18 was 89%. Here, the gap a between the inner circumferential surface 12b of the container body 12 was set to 2 mm.
[0147] [Test Example 19] In the first step of Test Example 18, 5.82 g of sodium metaborate (NaBO2), 3.18 g of aluminum powder, 1.86 g of sodium fluoride powder (NaF), and 0.1 g of sodium hydroxide powder were added, and the heating temperature in the third step was changed to 530°C. Except for this, the same operation as in Test Example 17 was performed to obtain sodium borohydride (SBH). The Na / B (molar ratio) in Test Example 19 was 1.50. As a result, the time lag was 2.33 Hr. The reaction rate at a reaction rate of 10% was 47% / Hr. The reaction rate (SBH rate) was 84.5% when the stirring time was 19.1 hours. The height ratio of Test Example 19 was 87%. Here, the gap a with the inner peripheral surface 12b side of the container body 12 was 2 mm.
[0148] [Test Example 20] In the first step of the test example 5, a closed container 10D equipped with a ribbon-shaped scraper 36 as shown in FIG. 7 was used, 17.46 g of sodium metaborate (NaBO2), 11.45 g of aluminum powder, 1.86 g of sodium fluoride (NaF), and 0.31 g of sodium hydroxide powder were added, the heating temperature in the third step was changed to 530°C, the peripheral speed was set to 15.76 cm / s (60 rpm), and stirring was performed for 18.6 hours. The same operation as in the test example 5 was performed to obtain sodium borohydride (SBH). The Na / B (molar ratio) of the test example 20 was 1.20. As a result, the reaction rate (SBH rate) was 91.17%. The height ratio of the test example 20 was 94%. Here, the gap a between the inner peripheral surface 12b side of the container body 12 was set to 2 mm.
[0149] [Test Example 21] In the first step of Test Example 5, 17.46 g of sodium metaborate (NaBO2), 11.45 g of aluminum powder, 1.86 g of sodium fluoride (NaF), and 0.31 g of sodium hydroxide powder were added, and the heating temperature in the third step was changed to 490°C, and the peripheral speed was changed to 7.8 cm / s (30 rpm). Except for this, sodium borohydride (SBH) was obtained in the same manner as in Test Example 5. The Na / B (molar ratio) of Test Example 21 was 1.17. As a result, the reaction rate at a reaction rate of 10% was 131% / Hr. The reaction rate (SBH rate) was 86.7%. The height ratio of Test Example 21 was 87%. Here, the gap a between the inner peripheral surface 12b side of the container body 12 was set to 2 mm.
[0150] [Comparative Example 8] In Test Example 18, sodium borohydride (SBH) was obtained by the same operation as in Test Example 17, except that 5.82 g of sodium metaborate (NaBO2), 3.81 g of aluminum powder, 0.62 g of sodium fluoride (NaF), and 1.06 g of sodium hydroxide powder were added. The Na / B (molar ratio) in Comparative Example 8 was 1.47. As a result, the reaction rate at a reaction rate of 10% was 8.3% / Hr. The reaction rate (SBH rate) was 32.4%. The height ratio in Comparative Example 8 was 89%. Here, the gap a with the inner peripheral surface 12b side of the container body 12 was set to 2 mm.
[0151] [Comparative Example 9] In Test Example 20, 5.82 g of sodium metaborate (NaBO2), 3.81 g of aluminum powder, 0.62 g of sodium fluoride (NaF), and 0.29 g of sodium hydroxide powder were added, and the heating temperature in the third step was changed to 478°C. Except for this, the same operation as in Test Example 19 was performed to obtain sodium borohydride (SBH). The Na / B (molar ratio) in Comparative Example 9 was 1.19. As a result, the reaction rate at a reaction rate of 10% was 2.0% / Hr. The reaction rate (SBH rate) was 19.6%. The height ratio of Comparative Example 9 was 87%. Here, the gap a between the inner peripheral surface 12b side of the container body 12 was set to 2 mm.
[0152] The results of Test Examples 18 to 20 and Comparative Examples 8 and 9 are shown in Table 4.
[0153] [Table 4]
[0154] As shown in Table 4, sodium hydroxide was added in Test Examples 18 to 20, but the Na / B ratio was set to 1.5 or less. When the Na / B ratio was high, such as 1.50 in Test Example 19, the SBH conversion rate was slightly low at 84.9%, but when the Na / B ratio was around 1.2, it was good at 86.7%-91.1%. In Test Example 18, the mixing time was short at 5.0 hours, resulting in a low SBH conversion rate. On the other hand, in Comparative Example 8, although Na / B was 1.47, the reaction rate was significantly reduced to 32%. This is because the amount of sodium hydroxide added was large, and under these test conditions, sodium borate formed a hydrate, and moisture removal was insufficient. In addition, since the Na / B (molar ratio) was increased to 1.47 using sodium hydroxide, mass transfer occurred by diffusing in a sherbet-like state, the reaction rate slowed down, and the reaction rate of sodium boron (SBH) decreased. In addition, when the heating temperature was as low as 478°C as in Comparative Example 9, mass transfer occurred only by diffusion within the solid because sodium borohydride was a solid and did not serve as a medium for the transfer of various ions, and the reaction rate significantly decreased, and the reaction rate of sodium boron (SBH) decreased.
[0155] Here, when a small amount of sodium hydroxide is added, the surface of aluminum is oxidized by the water generated to form a new thin aluminum oxide film, and sodium oxide is also produced at the same time, so the aluminum oxide film changes to sodium aluminate (NaAlO2), and then it becomes easy to change to iota alumina by fluoride ions. In addition, some of the water becomes hydrogen fluoride, which has the effect of forming a NaAlF layer on the aluminum surface. However, when a large amount of sodium hydroxide is mixed as in Comparative Example 8, a thick sodium aluminum dioxide (NaAlO2) layer is generated, and the generation of moisture continues for a long time, causing the generation of fine crystal hydrates, which maintains a high oxygen partial pressure in the system, causing the aluminum oxidation reaction and the hydride generation reaction to compete with each other, resulting in a decrease in the reaction rate and reaction rate.
[0156] Fig. 11 is an X-ray diffraction analysis chart of a product tested under the same conditions as in Test Example 18 and stopped at a reaction rate of 8.1% immediately after the start of the reaction. Fig. 12A and Fig. 12B are SEM mapping photographs of a product tested under the same conditions as in Test Example 18 and stopped at a reaction rate of 8.1% immediately after the start of the reaction.
[0157] In the early stage of the particle stirring reaction, the X-ray diffraction analysis in Figure 11 confirms the production of Na3AlF6 and sodium borohydride. It was found that Na3AlF6 was produced in the early stage of the reaction. The "F map" of the SEM mapping in Figure 12B also revealed that a fluoride layer had formed on the surface of the aluminum particles. This is presumed to be a fluoride layer mainly containing Na3AlF6. This fluoride layer is called the "NaAlF layer."
[0158] Thick layers of aluminum and sodium oxides can be seen around this NaAlF layer in many places. When the oxides are observed under magnification, needle-shaped crystals can be seen. The needle-shaped crystals are thought to be iota alumina. Sodium metaborate is seen adhering around the oxides.
[0159] It is speculated that the reaction begins around the NaAlF layer, and as a result an SBH is formed with the iota-alumina layer, sodium borate adheres to the iota-alumina layer, sodium oxide and boric acid are supplied from the sodium borate through the iota-alumina layer, and a synthesis reaction of sodium borohydride occurs between aluminum and hydrogen.
[0160] FIG. 13 is an X-ray diffraction analysis chart of the product in Test Example 20 with a reaction rate of 91.1%. From the X-ray diffraction analysis of the product of the reaction that was almost completed (reaction rate 91.1%), the product was sodium borohydride and Na 0.67 Al6 O 9.33 It was found that the main component was alumina with the composition. The excess aluminum added from the reaction formula, the additive aluminum fluoride, and cryolite (Na3AlF6) observed as a product in the initial reaction were identified. Na 0.67 Al6 O 9.33 has a diffraction profile almost identical to that of mullite, and is believed to have the same crystal structure. This crystal is determined to be iota alumina. Fluoride is known as a catalyst for promoting the crystallization of alumina, and is believed to have the effect of promoting the crystal growth of iota alumina. Some of the fluoride is observed as cryolite with a diffraction intensity unchanged from the initial stage, and most of the fluoride shows a diffraction intensity indicating that it exists as sodium fluoride.
[0161] [Test Example 22] In the second step of Test Example 17, a vacuum pump was connected to the sealed container containing the raw material, and the container was heated to 530°C to remove moisture for 0.73 hours, and hydrogen gas was introduced to 0.76 MPa. After the third step was performed at 530°C, stirring was stopped, and after-baking was performed at 530°C. The same operation as in Test Example 18 was performed to obtain sodium borohydride (SBH). The Na / B (molar ratio) of Test Example 22 was 1.21. As a result, the reaction rate calculated from the slope of the graph of the reaction rate was 133% / Hr when the reaction rate was 0.1. The time lag was 1.21Hr. The reaction time was 11.3 hours. The reaction rate (SBH rate) was 89.9%. The height ratio of Test Example 22 was 87%. Here, the gap a between the inner circumferential surface 12b side of the container body 12 was 2 mm.
[0162] [Test Example 23] In Test Example 21, sodium borohydride (SBH) was obtained by the same operation as Test Example 21, except that, before the third step, pre-baking was performed in a hydrogen atmosphere at 530°C for 2.4 hours in a sealed container as the second step, and then stirring was started at 531°C and performed for 5.5 hours in the third step. The Na / B (molar ratio) in Test Example 21 was 1.21. As a result, the time lag was 1.5Hr. The reaction rate when the reaction rate was 10% was 144% / Hr. Since the reaction rate when the reaction rate was 0.3 was as fast as 211% / Hr, the stirring time in the third step was shortened to 5.5 hours. The reaction rate (SBH rate) in Test Example 23 was 95.5%. The height ratio of Test Example 23 was 87%. Here, the gap a with the inner circumferential surface 12b side of the container body 12 was set to 2mm.
[0163] The results of Test Example 22 to Test Example 23 are shown in Table 5, Figure 18, and Figure 19. Figure 18 is a diagram showing the manufacturing conditions of Test Example 22. Figure 19 is a diagram showing the manufacturing conditions of Test Example 23. In Test Example 22, after the second step at 530 °C for 0.73 hours was completed, hydrogen gas was introduced, the pressure was set to 0.76 MPa, and stirring was started. The hydrogen pressure dropped rapidly after a time lag of 1.2 hours, and the particle stirring reaction started. The reaction rate dropped once when the reaction rate was around 0.23, and then the reaction rate returned to normal. This indicates that the reaction was carried out by stirring and mixing in a state where the particles were stuck together like bread dough, rather than in a particulate state. After 6.4 hours had elapsed since the start of heating, the stirring was stopped at a reaction rate of 0.78, and the reaction was continued by after-baking in a stationary state. The heating was stopped about 13 hours after the start of heating. The reaction continued even when the stirring was stopped, and the final reaction rate was 89.9%. It was also found that the reaction rate improved when the hydrogen gas pressure was increased. Test Example 23 was the same as Test Example 22, except that hydrogen gas was introduced instead of the vacuum moisture removal in the second step, and the reaction was carried out for 2.3 hours. The time lag was slightly longer at 1.5 hours, but the reaction rate of the particle stirring reaction in the third step was greatly improved, and the reaction rate improved at a reaction rate of 0.25 or more, and the reaction time in the third step was shortened from 11.3 hours to 5.5 hours. In Test Example 23, the reaction progressed with after-baking even when the reaction rate was 0.9 or more.
[0164] [Table 5]
[0165] From the results of Test Example 22, the reaction continued even if after-baking was performed without stirring after the third step, and a reaction rate of about 90% was obtained. Compared to Test Example 20, the reaction rate was improved and the stirring time was shortened by performing pre-baking. From the results of Test Example 23, when hydrogen gas heating treatment was performed in the second step and after-baking was performed after the third step, the reaction rate and reaction rate (SBH rate) were improved compared to Test Example 20. It can be assumed that the improvement was due to the particle stirring reaction being carried out for a long period of time. 18 and 19, an improvement in the reaction rate due to after-baking was confirmed even when no stirring was performed after the reaction in the third step was completed in Test Examples 22 and 23. It is believed that the reaction proceeded even with after-baking in a stationary state because the amount of sodium borate particles necessary for the reaction was adhered to the aluminum particles after sufficient particle stirring reaction had occurred.
[0166] [Test Example 24] In the second step of the test example 2, a moisture removal treatment was performed in a vacuum atmosphere at 510°C for 1.5 hours, and then hydrogen gas was introduced and set to 0.82 MPa. In the third step, the heating temperature was set to 510°C and stirring was performed. The same operation as in the test example 2 was performed to obtain sodium borohydride (SBH). The Na / B (molar ratio) of the test example 24 was 1.19. As a result, the time lag was 1.98 Hr. The reaction rate (SBH rate) was 101.9%. The height ratio of the test example 24 was 89%. Here, the gap a with the inner peripheral surface 12b side of the container body 12 was set to 2 mm.
[0167] [Test Example 25] In Test Example 24, before the third step, a moisture removal treatment was performed in a vacuum atmosphere at 510°C for 2.4 hours as the second step, and then stirring and heating were started at 510°C in the third step. Except for this, sodium borohydride (SBH) was obtained in the same manner as in Test Example 24. The Na / B (molar ratio) of Test Example 25 was 1.19. As a result, the time lag was 1.1 Hr. The reaction rate (SBH rate) was 103.6%. The height ratio of Test Example 25 was 89%. Here, the gap a with the inner peripheral surface 12b side of the container body 12 was set to 2 mm.
[0168] [Test Example 26] In Test Example 24, before the third step, a heat treatment was performed in an air atmosphere at 350°C for 1.2 hours as the second step, and then stirring was started and heating was performed at 510°C in the third step. Except for this, the same operation as in Test Example 2 was performed to obtain sodium borohydride (SBH). The Na / B (molar ratio) of Test Example 26 was 1.19. As a result, the time lag was 3.1 Hr. The reaction rate (SBH rate) was 102.4%. The height ratio of Test Example 26 was 89%. Here, the gap a with the inner peripheral surface 12b side of the container body 12 was 2 mm.
[0169] [Comparative Example 10] In Test Example 21, NaF was not added, and 17.46 g of sodium metaborate (NaBO2), 12.5 g of aluminum powder, and 2.00 g of sodium hydroxide powder were added. Before the third step, pre-baking was performed in a vacuum atmosphere at 530°C for 4.0 hours as the second step, and then stirring was started at 520°C in the third step, and heating was performed. The same operation as in Test Example 21 was performed to obtain sodium borohydride (SBH). The Na / B (molar ratio) of Comparative Example 10 was 1.19. As a result, the reaction rate (SBH rate) was 14.1%. The height ratio of Comparative Example 10 was 87%. Here, the gap a with the inner peripheral surface 12b side of the container body 12 was set to 2 mm.
[0170] [Comparative Example 11] In Test Example 21, sodium fluoride and sodium hydroxide were not added, but 4.69 g of sodium metaborate powder (NaBO2), 1.66 g of sodium diborate powder, and 3.82 g of aluminum powder were added, and before the third step, pre-baking was performed in a vacuum atmosphere at 530°C for 1.3 hours as the second step, and then stirring was started at 530°C in the third step and heating was performed. Sodium borohydride (SBH) was obtained by the same operation as in Test Example 21. The Na / B (molar ratio) in Comparative Example 11 was 1.19. As a result, the reaction rate at a reaction rate of 10% was 3.9% / Hr, and the final reaction rate (SBH rate) was 42.5%.
[0171] The results of Test Examples 22 to 26, Comparative Example 10 and Comparative Example 11 are shown in Table 5.
[0172] In Test Examples 22 and 23, a pre-bake was performed, which was a long heat treatment time longer than the conditions required for removing moisture (heating at about 500°C for 0.5 hours), and an after-bake was performed, which allowed the reaction to continue in a stationary state. Compared to Test Example 20, in which no pre-bake was performed, the reaction rate improved and the mixing time could be shortened. The product after the particle agitation reaction could be allowed to proceed with the reaction by after-bake without agitation.
[0173] From the results of Test Examples 24 to 26, the reaction rate (SBH rate) was improved by about 1.1 times compared to Test Example 2 by pre-baking as the second step, setting the temperature in the third step to 510°C, and increasing the hydrogen pressure. Pre-baking can shorten the time lag by vacuum heating treatment compared to atmospheric treatment, and the total synthesis time can be shortened. In addition, since the reaction rate exceeded 100% in these tests, the SBH reaction rate was examined by iodine titration, and it was 97.3% in Test Example 24. The reaction rate was high. This indicates that the hydrogen gas was consumed in the form of sodium hydride. It is thought that the generation of sodium hydride in the high reaction rate region is not a reduction reaction between aluminum and hydrogen in sodium oxide (Na2O), but a reduction reaction caused by the generation of low-grade aluminum fluoride in the NaAlF layer proceeds.
[0174] FIG. 14 is an X-ray diffraction analysis chart of the product of Comparative Example 10 with a reaction rate of 14.1% when NaOH was added. FIG. 15 is an SEM mapping photograph of the product of Comparative Example 10 with a reaction rate of 14.1% when 2.0 g of NaOH was added. As shown in FIG. 14, in the particle stirring method in which stirring is performed only with a stirrer without using a stirring medium, when the alkalinity is increased only with NaOH without adding NaF when increasing the Na / B ratio, the reaction rate becomes very low, and the reaction rate is 14.1%. From the X-ray diffraction chart of the product of FIG. 14 in which NaOH was added to Na / B=1.2 and stirring was performed for 35 hours with a reaction rate of 14.1%, sodium borohydride and sodium aluminate (NaAlO2) were detected as products. Iota alumina was not detected. In addition, sodium aluminum hydrate and sodium boron hydride hydrate were detected, and it was found that moisture remained. It is speculated that the low reaction rate and reaction rate are due to the oxidation of the aluminum surface by the moisture supplied from these hydrates. From the SEM mapping composite photograph shown in FIG. 15 of Comparative Example 10, it is confirmed that the surface of the aluminum particles is covered with sodium aluminum oxide.
[0175] AlB2 is formed inside the aluminum, and small amounts of sodium borohydride are also formed in the oxide parts inside the cracks in the aluminum. Sodium metaborate is adhered to the outside of the sodium aluminum oxide. It is highly likely that this sodium aluminum oxide is sodium aluminum dioxide (NaAlO2) as detected by X-ray diffraction analysis. The surface of this oxide is dense but has cracks in places, and some of it exists within the sodium metaborate particles that have broken off. From these conditions, it is speculated that although this oxide is dense, it is easily broken and torn off when deformed.
[0176] From the standpoint of ion conduction, even if sodium metaborate is attached, the production of sodium borohydride is small after 35 hours of reaction. It is estimated that sodium aluminum dioxide (NaAlO2) has almost no ion mobility. Therefore, it is estimated that Na2O cannot move as an intermediate medium, and very little NaH is produced on the aluminum surface. The lack of Na2O on the aluminum surface is also supported by the production of AlB2 in the aluminum. [Explanation of symbols]
[0177] 10A~10E Sealed container 12 Container body 12a bottom 14 Lid 16 Heater 18 O-ring 20 Motor 22 Stirring rod 22a bottom 22b Inner surface 22A Stirrer 22B J type stirring section 24 No. 1 Pipe 26 Hydrogen gas supply valve 28 Exhaust valve 30 No. 2 Pipe 32 Pressure gauge 35 Scraper 36 Ribbon scraper 37 Wide Paddle 39 Raw materials 51 Sodium borates 52 Aluminum Powder 53 Non-oxidizing gases 54 Fluoride 101 Aluminum 101a surface 101b Al oxide film 101c Needle-shaped iota alumina (0.67Na 6Al 9.33O) layer 102 Sodium metaborate (NaBO2) 103 Sodium Fluoride (NaF) 111 Sodium borohydride (SBH) 112 Sodium hydride (NaH) 113 Sodium oxide (Na2O) 115 Reactant layer (sodium borohydride (SBH), sodium hydride (NaH))
Claims
1. In a sealed container filled with hydrogen gas, sodium borates, aluminum powder, and fluoride powder are mixed and reacted at 560° C. or less. Stirring is performed using a stirrer in the sealed container, A minimum gap (a) between the stirrer and the bottom of the sealed container in the gravity direction; a mixing height ratio (X) represented by the following mathematical formula (I) based on a raw material charging height (b) at which the raw material is charged into the sealed container, is 77% or more. X = [(b - a) / b] x 100 ... formula (I)
2. In claim 1, 13. A method for producing sodium borohydride, wherein the sodium borates are one or more selected from the group consisting of sodium metaborate and sodium tetraborate.
3. In claim 1 or 2, The fluoride is sodium fluoride (NaF), sodium hexafluoroaluminate (Na 3 AlF 6 ), potassium fluoride (KF), potassium aluminum fluoride (KAIF 4 ), aluminum fluoride (AlF 3 ), and lithium fluoride (LiF).
4. In any one of claims 1 to 3, 3. A method for producing sodium borohydride, wherein the aluminum in the aluminum powder has a molar ratio of aluminum to boron in the sodium borates of 4 / 3 or more.
5. In any one of claims 1 to 4, Further, an alkali metal oxide or an alkaline earth metal oxide is added, a molar ratio of a sum of molar amounts of an alkali metal and an alkaline earth metal and an alkali metal and an alkaline earth metal contained in the sodium borates to a molar amount of boron contained in the sodium borates is 1.0 or more and 1.4 or less.
6. In any one of claims 1 to 5, The method for producing sodium borohydride, further comprising heat-treating the inside of the sealed container at 280° C. or higher and 560° C. or lower before stirring.
Citation Information
Patent Citations
Method for producing sodium borohydride
JP2019189483A
Method for producing sodium borohydride
JP2809666B2
Method and device for producing sodium borohydride
WO2015190403A1